Don Juan DeMarco - Leven, Jeremy; Brando, Marlon, 1924-2004; Johnny Depp; Faye Dunaway; Géraldine Pailhas; Bob Dishy; Rachel Ticotin; Talisa Soto; Marita Geraghty; Richard C Sarafian; Tresa Hughes; Stephen Singer; et al. (USA American Zoetrope, 1995)
A psychiatrist must cure a young patient that presents himself as Don Juan, the greatest lover in the world.
A young man (who is the legendary Don Juan?), comes to New York in search of his lost love. Feeling like he has nothing to live for, he attempts to commit suicide from atop a billboard. Dr. Mickler, (played by Marlon Brando), is a soon retiring psychiatrist who helps Don Juan (Johnny Depp), come to his senses. He brings the costumed boy to the psychiatric hospital , in hopes of helping Don Juan find his identity. The doctor works with him for ten days, in which Don tells his life story. Mickler begins to believe that the young man is truly Don Juan, but the rest of the staff doesn't agree. The doctor knows that the only way out for Don Juan, is to pretend he's an average boy whose fantasy got the best of him.
The story of the man who thought he was the greatest lover in the world... and the people who tried to cure him of it!
Languages : Turkish, English
Subtitle : Turkish
Keywords: Comedy; Drama; Romance